2000
DOI: 10.1002/jlb.67.2.183
|View full text |Cite
|
Sign up to set email alerts
|

Serglycin secreted by leukocytes is efficiently eliminated from the circulation by sinusoidal scavenger endothelial cells in the liver

Abstract: This study was undertaken to determine the fate of the circulating chondroitin sulfate proteoglycan serglycin. The human monocytic cell line THP-1 was cultured under serum-free conditions in the presence of [35S]sulfate. The conditioned medium was harvested and 35S-macromolecules were purified by Q-Sepharose anion-exchange chromatography and Superose 6 gel chromatography. After labeling with 125I, the purified material was treated with chondroitinase ABC and subjected to sodium dodecyl sulfate polyacrylamide g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 40 publications
(40 reference statements)
2
35
0
Order By: Relevance
“…These experiments were repeated several times with almost identical results. In all experiments, the bound fraction contained mainly the 300-kDa pro-MMP-9⅐PG heteromer but in some experiments also a heteromer with an M r Ͼ 10 6 . To summarize, 15-35% of the pro-MMP-9⅐PG heteromers were bound to gelatin-Sepharose.…”
Section: Intact Pg But Not Free Cs Chains Prevents Soluble Gelatin Frmentioning
confidence: 83%
See 1 more Smart Citation
“…These experiments were repeated several times with almost identical results. In all experiments, the bound fraction contained mainly the 300-kDa pro-MMP-9⅐PG heteromer but in some experiments also a heteromer with an M r Ͼ 10 6 . To summarize, 15-35% of the pro-MMP-9⅐PG heteromers were bound to gelatin-Sepharose.…”
Section: Intact Pg But Not Free Cs Chains Prevents Soluble Gelatin Frmentioning
confidence: 83%
“…However, when monocytes are stimulated and differentiated to macrophages, both the biosynthesis and the secretion of CSPG are increased (4). The human monocyte cell line THP-1 secretes PGs such as versican, perlecan, and serglycin (5,6). The biological role of the secreted PGs such as serglycin from macrophages is not clear, but it has been shown that it binds to other molecules released from the cells through interaction with the GAG chains (7,8), suggesting that this and other PGs may act as a kind of carrier molecule.…”
mentioning
confidence: 99%
“…Extracts were prepared from non-stimulated spleen cells (empty symbols) and from ConA-stimulated (3 days) spleen-derived CTLs predominantly highly sulfated GAGs of heparin type ([IdoUA-GlcNAc] n carbohydrate backbone) (36), whereas bone marrow-derived mast cells synthesize GAG chains of equally high charge density albeit of chondroitin sulfate type ([GlcUA-GalNAc] n carbohydrate backbone) (37). In contrast, SG produced by macrophages (38) and NK cells (17) contain chondroitin sulfate chains of much lower charge density.…”
Section: Discussionmentioning
confidence: 99%
“…N-terminal sequencing of serglycin isolated from conditioned media of two different monocyte cell lines revealed extensive processing of the core protein N terminus (12,13). However, it is not known whether the N-terminal processing of serglycin has any functional consequence.…”
Section: Structural Diversity Of Serglycinmentioning
confidence: 99%